Etnhobotanical Insights into Traditional Medicine: A Study of Medicinal Plants in Sungai Betung, Kerinci Regency - Delfia, Veli; Radhwa, Yuli Nur; Fia, Meli Gesto; Setiawan, M. Eval (Biology and Education Journal, 2026)
The purpose of this study is to document the types of traditional medicinal plants used by the community of Sungai Betung, Kerinci Regency, and to examine how these plants are utilized in daily traditional treatment practices. The research employed a descriptive-exploratory qualitative method through interviews and direct observations with four informants who possess extensive knowledge of medicinal plants. The findings identified 20 species of medicinal plants classified into four major categories: digestive disorders, skin wounds and infections, musculoskeletal problems, and specific physiological conditions. These results indicate that the community’s ethnobotanical knowledge remains strong and has the potential to be applied as a safe and natural alternative source of traditional medicine.